Morphology of the vas deferens of the budgerigar (Melopsittacus undulatus) - Baldan, C.; Orsi, A. M. [UNESP]; Viotto, M. J. S.; Baraldi-Artoni, S. M. [UNESP]; Stefanini, M. A. (My University, 2003)
A morphological study of the budgerigar vas deferens was conducted to demonstrate the electron-microscopic features of its epithelial lining. The analysis showed that the vas deferens of the budgerigar was found to be of a tubular and serpentine structure, continuous with the epididymal region and lined with stereo ciliated pseudostratified epithelium, which contained folds projecting into the tubular lumen and a characteristic brush border. The epithelium consists of ciliated and non-ciliated cells with different electron densities. Ciliated cells were characterized by two morphologically distinct configurations: some cells were columnar and other ciliated cells were longer, thinner and dark. Non-ciliated cells showed apical cytoplasmic expansions, which projected into the tubular lumen as protrusions.
Keywords: Aves; Birds; Budgerigar; Epithelium; Morphology; Vas deferens; bird; cell structure; cytoplasm; electron microscopy; epididymis; epithelium; melopsittacus undulatus; morphology; nonhuman; vas deferens; Melopsittacus undulatus